Analisis Pengelolaan Persediaan Pada PT ABC (JURNAL ULET (Utility, Earning and Tax), 2023)
The purpose of this study is to determine and analyze the management of partner cooking oil inventories applied by PT Irian Jaya Sehat, using descriptive research methods, and data collection techniques, namely interviews and documentation. To analyze inventory, the Economic Order Quantity (EOQ) method is used. The results showed that the inventory control implemented by PT Irian Jaya Sehat was not optimal because the company had run out of stock. PT Irian Jaya Sehat should try to apply the EOQ  method in terms of inventory control so that the company can minimize inventory costs.